2019
DOI: 10.2147/mder.s165620
|View full text |Cite
|
Sign up to set email alerts
|

<p>IN.PACT<sup>TM</sup> Admiral<sup>TM</sup> drug-coated balloons in peripheral artery disease: current perspectives</p>

Abstract: Endovascular therapy has evolved as a main treatment option especially in patients with short (<25 cm) femoropopliteal lesion. The latest guideline recommends the use of drugeluting devices (both drug-coated balloons [DCBs] and drug-eluting stents) in short femoropopliteal lesions as class IIb recommendation. DCB usage is also recommended for in-stent restenosis lesions (class IIb). DCBs are a more attractive treatment option because the lack of metal prosthesis allows for more flexibility in future treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 69 publications
(88 reference statements)
0
12
0
Order By: Relevance
“…Endovascular treatment of long occlusive arterial lesions remains complicated and requires further research and development [ 1 10 12 17 ]. The popularization of DCB has led to significant improvement in treatment outcomes for femoropopliteal artery lesions [ 2 4 8 9 ]. However, more favorable long-term patency after bypass surgery is reported for long and complex vascular lesions classified as TASC II C or D [ 5 7 10 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endovascular treatment of long occlusive arterial lesions remains complicated and requires further research and development [ 1 10 12 17 ]. The popularization of DCB has led to significant improvement in treatment outcomes for femoropopliteal artery lesions [ 2 4 8 9 ]. However, more favorable long-term patency after bypass surgery is reported for long and complex vascular lesions classified as TASC II C or D [ 5 7 10 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the treatment of femoropopliteal artery stenosis, balloon angioplasty has been recognized as the first-line treatment for short femoropopliteal artery segments of <50 mm or simple lesions classified as the Trans-Atlantic Inter-Society Consensus Document on Management of Peripheral Arterial Disease (TASC II) A or B. However, the treatment outcome is poorer for long and complex lesions classified as TASC C or D and inferior to traditional bypass surgery, even to prosthetic graft [ 4 5 6 ]. This is because patients with long femoropopliteal artery stenosis or occlusion often have multiple inflow or outflow lesions; recoiling stenosis due to severe calcification or total chronic occlusion can easily occur in such patients [ 6 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacokinetic profile of Lutonix was found to have a lower PTX tissue bioavailability compared to IN.PACT (Medtronic, Minneapolis MN, USA) and Stellarex DCB (Philips, Amsterdam, The Netherlands) after 28 days. 37 This might have attributed to lower primary patency and freedom from TLR at 1-year follow-up in the LEVANT 2 study published in 2015. 38,39 More recently, the COMPARE multicenter RCT (NCT02701543) examined two DCB and showed that the Ranger DCB (Boston Scientific, Marlborough, MA, USA) was comparable with the IN.PACT DCB for the treatment of symptomatic femoropopliteal lesions.…”
Section: Clinical Use Of Dcb In Peripheral Artery Disease (Pad)mentioning
confidence: 99%
“…Recoils upon standard percutaneous angioplasty (PTA) lead to the necessity of deploying additional devices, including atherectomy, as well as implantation of stents [4], with the consequence of longer procedure durations, material costs and radiation exposure, as well as a prolonged antithrombotic treatment regime and thus, bleeding risk [5]. Drug-eluting balloons (DEB) have also failed to markedly improve patency in such calcified lesions, probably due to insufficient diffusion of the antiproliferative medication through the barrier of the calcified vessel wall [6][7][8][9]. Hence, there is a valid notion that a careful indentation of the target lesion using scoring balloons with built-in helical nitinol elements a more atraumatic preparation and higher lumen gain of the target vessel could be achieved, thus minimizing the rate of periprocedural complications and additional procedures [10].…”
Section: Introductionmentioning
confidence: 99%